The world meteorological organization Tenth International Workshop on tropical cyclones (IWTC-10): A summary - Robert Rogers; Joseph Courtney; Kimberly Wood (Tropical Cyclone Research and Review, 2023)
The Tenth International Workshop on Tropical Cyclones (IWTC-10) occurred from 5 to 9 December 2022 in Bali, Indonesia. This workshop continued the goal of the original IWTC, held in 1985 in Bangkok, Thailand, to bring together forecasters and researchers from countries around the world that are impacted by tropical cyclones (TCs) to discuss the latest research and forecast advances and share best practices to improve TC forecasts globally. The workshops have continued as a regular feature of WMO efforts to encourage the advancement of TC forecasting and improve ways of communicating TC hazards to the general public.Global TC forecasting efforts in the past 10–15 years have emphasized hazards and impacts of landfalling TCs beyond just track and intensity. Additionally, there has been a growing interest in improving the communication of these hazards and impacts, using concepts from social and behavioral sciences, in ways that can lead to effective decision-making from stakeholders (e.g., government officials, emergency managers, media, general public). As such, the theme for IWTC-10 was “Improved TC science and services for better decision-making.” More about this theme, how the workshop was structured around it, and key outcomes from the workshop are discussed in this summary article.